Limitasi Hak Mengundurkan Diri Calon Anggota Legislatif Terpilih Menurut Putusan Mahkamah Konstitusi Nomor 176/PUU-XXII/2024 Perspektif Siyasah Dusturiyah - Rama Raihan Faturrohman; Chaerul Shaleh; Taufiq Alamsyah (Jurnal Hukum Lex Generalis, 2025)
The Constitutional Court Decision Number 176/PUU-XXII/2024 is a judicial response to the normative vacuum regarding the right of elected legislative candidates to resign, as previously unregulated in Law Number 7 of 2017 concerning General Elections. The right to resign, which was previously not strictly limited, has created a loophole for abuse of power that negatively impacts the integrity of elections and the sovereignty of the people. This study aims to analyze the limitation of this right through three main approaches: constitutional-legal analysis, legal implications, and the perspective of siyasah dusturiyah. The research method used is a normative and conceptual legal approach, strengthened by analysis of Constitutional Court decisions, scholarly articles, and Qur'anic interpretation. The findings indicate that restricting the right to resign aligns not only with the principles of constitutional democracy and legal justice but also with the principles of trust (amanah) and justice in Islamic political jurisprudence. The verse QS Al-Ahzab [33]:72 provides a normative basis affirming the importance of exercising entrusted power with justice. Therefore, the state is obligated to formulate technical regulations as an implementation of the decision to ensure the protection of the people's votes and to prevent the manipulation of legislative power by political actors.